2018
DOI: 10.1155/2018/8258096
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Early Postoperative Feeding in Gastrointestinal Anastomotic Fistula Formation and Healing Time in Rabbits

Abstract: Objectives To determine whether early postoperative feeding attenuates the inhibitory effects of intestinal anastomosis in rabbits. Methods After undergoing gastrointestinal anastomosis, 48 rabbits were randomly divided into experimental and control groups. The rabbits in the experimental group were fed a liquid diet beginning 24 h postoperatively, while the control rabbits received only total parenteral nutrition after the operation. Exploratory laparotomies were performed on four rabbits in each group 3, 5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…9 Based on observations of how mucosal tissue heals within the first 48 h and the success of Enhanced Recovery After Surgery protocols in gastrointestinal surgery involving bowel anastomosis, it is reasonable to hypothesize that early oral feeding may also be a feasible option following laryngectomy. 10,11 Indeed, a number of studies over the last two decades have reported comparable outcomes between early and late oral feeding regimes. [12][13][14][15][16][17] A previous systematic review examining the relationship between PCF and time of oral feeding in eight studies (four randomized controlled trials (RCTs) and four cohort studies) concluded that there were no differences in PCF rates between those fed before the fifth day and those fed after the seventh day.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Based on observations of how mucosal tissue heals within the first 48 h and the success of Enhanced Recovery After Surgery protocols in gastrointestinal surgery involving bowel anastomosis, it is reasonable to hypothesize that early oral feeding may also be a feasible option following laryngectomy. 10,11 Indeed, a number of studies over the last two decades have reported comparable outcomes between early and late oral feeding regimes. [12][13][14][15][16][17] A previous systematic review examining the relationship between PCF and time of oral feeding in eight studies (four randomized controlled trials (RCTs) and four cohort studies) concluded that there were no differences in PCF rates between those fed before the fifth day and those fed after the seventh day.…”
Section: Introductionmentioning
confidence: 99%
“…Based on observations of how mucosal tissue heals within the first 48 h and the success of Enhanced Recovery After Surgery protocols in gastrointestinal surgery involving bowel anastomosis, it is reasonable to hypothesize that early oral feeding may also be a feasible option following laryngectomy 10,11 . Indeed, a number of studies over the last two decades have reported comparable outcomes between early and late oral feeding regimes 12‐17 …”
Section: Introductionmentioning
confidence: 99%
“…The presence of flatus and BM are used to represent the end of POI and the ability of the postsurgical GI patient to tolerate oral food [8,10,20,24] . The postoperative LOS used as one of the evaluation indices of EOF [21] . In our study, early oral intake is associated with a shorter postoperative LOS and bowel function recovery quicker in the EOF group.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 cm before and after the cecum anastomotic line was fixed to a tensile test machine (an AG-X Plus Desktop 10 kN, Pneumatic Grip, Shimadzu, Japan) at a rate of 60 mm/min until rupture occurred. The weight necessary to break the anastomotic tissue was recorded as the tissue tensile strength ( 33 ).…”
Section: Methodsmentioning
confidence: 99%